PELANGGARAN HUKUM DALAM KELUARGA ISLAM: KAJIAN TENTANG ZHIHAR, ILA', DAN LI'AN - Asep Mahbub Junaedi; Wasman Wasman (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Three Islamic legal practices in the context of husband-wife relationships, namely Zhihar, Il'a, and Li'an, are actions that can result in divorce. Zhihar is an action that occurs when a husband utters words that are forbidden to his wife by comparing her to a part of his mother's body. Violations of Zhihar have the effect of prohibiting the husband from having intimate relations with his wife and the kafarat that must be fulfilled, such as freeing slaves, fasting, or giving food to the poor. Il'a, on the other hand, involves the husband promising not to have sexual relations with his wife for a certain period, giving time for both to reflect on their relationship. Violations of Il'a resulted in legal consequences, such as feeding ten poor people, distributing clothes, freeing slaves, or fasting for three days. Li'an is an oath given by a husband when accusing his wife of committing adultery without the evidence of four strong witnesses. If proven to be lying, they will receive severe punishment in accordance with Islamic law. Exploring the legal aspects and consequences of these practices illustrates the complexity of regulations and the enforcement of justice in the regulation of husband-wife relationships in Islam.